Using fruit peel as a substrate for the isolation, biosynthesis, and optimization of glucoamylase by Bacillus sp. under submerged fermentation - Kiran, Ayesha; Ghafoor Shahid, Memuna; Ullah, Najeeb; Sarwar, Abid; Tahir, Samraz; Nadeem, Muhammad; Nelofer, Rubina; Khan, Ayaz Ali; Aziz, Tariq; Shami, Ashwag; Al-Asmari, Fahad; A. Al-Joufi, Fakhria (Italian Journal of Food Science, 2025)
Glucoamylase is a fungal enzyme easily obtained by using a fungal strain—Aspergillus niger. The aim of this study was to isolate the bacterial strain and culture condition optimization to produce glucoamylase. This optimization was achieved under the submerged fermentation technique where fruit peel was used as substrate. The production of glucoamylase was carried out by using (w/v [weight in volume]) yeast extracts 1%, NaCl (chemical formula for sodium chloride) 0.5%, ZnSO4 (zinc sulfate) 0.5%, K2HPO4 (dipotassium phosphate) 0.5, and 1% fruit peel powder as substrate. The optimization of parameters was carried out by one factor at a time technique (OFAT) under submerged fermentation. Different carbon and nitrogen sources were screened for maximum enzyme activity. The physical and chemical parameters such as temperature, pH (potential of hydrogen), inoculum size, and salt concentrations were optimized to achieve the highest production. Based on the biochemical characterizations, the isolated strain was identified as Bacillus sp. FBA1 (fructose-bisphosphate aldolase 1). Maximum production of the enzyme was recorded at the 24th hour at 37°C temperature and pH was kept at 7.0. The salts combinations that produced the highest levels of glucoamylase production from Bacillus strain FBA1 were (g/L) NaCl 1, ZnSO4 1.5, FeSO4 (ferrous sulfate) 2, KH2PO4 (potassium dihydrogen phosphate) 2, CaCl2 (calcium chloride) 0.1, and MgSO4 (magnesium sulfate) 2. The optimum glucoamylase activity of 2.984 mg/mL/minute for FBA1 was obtained at pH 7 at 37°C. The results showed that fruit peels can be exploited as a potential substrate to produce glucoamylase at optimized conditions by Bacillus FBA1.